2010
DOI: 10.1159/000312817
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Ocular Toxicity in Ocular Application of Drugs and Chemicals – Part I: Animal Models and Toxicity Assays

Abstract: Aims: Experimental retinal research has gained great importance due to the ophthalmic pharmacotherapy era. An increasing number of drugs are constantly released into the market for the treatment of retinal diseases. In this review, animal species, animal models and toxicity assays in retinal research are discussed. Methods: An extensive search of the literature was performed to review various aspects of the methods of investigation of drug toxicity. The different types of animal species, as well as single anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 381 publications
(220 reference statements)
0
20
0
3
Order By: Relevance
“…We adopted a rabbit model previously described by Moshirfar et al [21]. It is widely accepted that the rabbit cornea responds similarly to the human cornea in terms of timing, the extent of scarring, and myofibroblast formation, and it has been used in research for many years [17]. Rabbit cornea is also convenient because of its similarity to the human cornea in size and the typically used epithelium debridement size is 5 or 6 mm, which is easy to follow [18-21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We adopted a rabbit model previously described by Moshirfar et al [21]. It is widely accepted that the rabbit cornea responds similarly to the human cornea in terms of timing, the extent of scarring, and myofibroblast formation, and it has been used in research for many years [17]. Rabbit cornea is also convenient because of its similarity to the human cornea in size and the typically used epithelium debridement size is 5 or 6 mm, which is easy to follow [18-21].…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo studies were performed because animals are still important for drug toxicity assessment prior to human use [17]. We selected a corneal wound healing model in rabbits, which is widely used in pre-clinical studies of the potential toxicity of various compounds applied topically [17-20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous laboratory investigations have shown that various changes in pH from solutions applied to the retina may cause toxicity [27]. In the retina, pH changes were found to strongly affect the retinal component of the c-wave and b-wave in the perfused cat eye model [28].…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit is heavily used in safety and toxicity studies of ocular therapeutics and potential toxins . To study the latter, a growing repertoire of in vitro tests have been developed .…”
Section: Key Animal Model Speciesmentioning
confidence: 99%